A soft edge target zone model: Theory and application to Hong Kong - Yu-Fu Chen; Michael Funke; Nicole Glanemann (Bank of Finland, Institute for Economies in Transition (BOFIT), 2009)
Hong Kong's currency is pegged to the US dollar in a currency board arrangement. In autumn 2003, the Hong Kong dollar appreciated from close to 7.80 per US dollar to 7.70, as investors feared that the currency board would be abandoned. In the wake of this appreciation, the monetary authorities revamped the one-sided currency board mechanism into a symmetric two-sided system with a narrow exchange rate band. This paper reviews the characteristics of the new currency board arrangement and embeds a theoretical soft edge target zone model typifying many intermediate regimes, to explain the notable achievement of speculative peace and credibility since May 2005.
URN:NBN:fi:bof-201408072187
Keywords: C61; E42; F31; F32; 330; currency board arrangement; target zone model; credibility; Hong Kong